Characterisation of CAH alleles with non-radioactive DNA single strand conformation polymorphism analysis of the CYP21 gene. Issue 3 (March 1997) - Bobba, A; Iolascon, A; Giannattasio, S; Albrizio, M; Sinisi, A; Prisco, F; Schettini, F; Marra, E
Abstract : The major cause of congenital adrenal hyperplasia (CAH), a common recessive genetic disease, is the deficiency of steroid 21-hydroxylase (21OH), a microsomal enzyme encoded by the CYP21 gene. Although several CAH causing mutations have been identified in the CYP21 gene of patients with 21OH deficiency, genotyping of the 21OH locus is quite complex because of the high frequency of gene conversion and the presence of multiple mutations on single CAH alleles. In order to perform the complete characterisation of the CYP21 gene coding region more simply, we developed a highly sensitive, non-radioactive method allowing DNA single strand conformation polymorphism (DNA-SSCP) analysis. This method was applied to the characterisation of all the exons and intron-exon junctions of the CYP21 gene in five patients affected by the simple virilising form and one affected by the salt wasting form. In all samples showing SSCP signals, direct sequence analysis showed the presence of more than one single sequence variant. In particular, four mutations which are already known to cause the disease, 16 polymorphisms, and one newly identified C to T transition at position 849 were detected. A random sequence analysis, performed on 31 out of 81 exons showing a normal SSCP pattern, shows the method to be highly sensitive: no sequence variant was detected, thus confirming the validity of this non-radioactive DNA-SSCP analysis in characterising the CYP21 gene in patients with steroid 21OH deficiency. Notwithstanding the complete characterisation of all exons and exon/intron junctions of the CYP21 gene, no complete genotype/phenotype correlation was found in the panel of patients analysed, thus suggesting that characterisation of CAH alleles must be extended to outside the coding region of the CYP21 gene, most probably into the promoter region.